Tokamak Plasma Flows Induced by Local RF Forces - 陈佳乐 高喆 (Plasma science & technology, 2015)
The tokamak plasma flows induced by the local radio frequency （RF） forces in the core region are analyzed. The effective components of local RF forces are composed of the momentum absorption term and the resonant parallel momentum transport term （i.e. the parallel component of the resonant ponderomotive forces）. Different momentum balance relations are em- ployed to calculate the plasma flows depending on different assumptions of momentum transport. With the RF fields solved from RF simulation codes, the toroidal and poloidal flows by these forces under the lower hybrid current drive and the mode conversion ion cyclotron resonance heating on EAST-like plasmas are evaluated.